Rozwiąż równania

a) 4x + 5 = 2x - 7

b) -3x +8 = 2x + 7

c) 3(y+ 2) = -2(y - 3)

d) 3x -7 = 27x + 11

e) 8 - 3x2 = 3x *(2 - x) -2x

f) (x + 3)(x - 4) = (x +2)(x - 1)


Odpowiedź :

Odpowiedź:

a) 4x-2x= -7-5

2x= -7-5

2x=-12

x=-6

b) -3x-2x=7-8

-5x=7-8

-5x= -1

x=[tex]\frac{1}{5}[/tex]

c) 3y+6=2y+6

3y= -2y

3y+2y=0

5y=0

y=0

d)3x-27x=11+7

-24=18

x=  - [tex]\frac{3}{4}[/tex]

e) 8-6=6x-3[tex]x^{2}[/tex]-2x

2=4x-3[tex]x^{2}[/tex]=0

3[tex]x^{2}[/tex]-4x+2=0

x=[tex]\frac{4+\sqrt{16-24} }{6}[/tex]

x= [tex]\frac{4+\sqrt{-8} }{6}[/tex]

x ∉R

f) [tex]x^{2}[/tex]-4x+3x-12=[tex]x^{2}[/tex]-x+2x-2

-4x+3x-12= -x+2x-2

-x-12=x-2

-x-x= -2+12

-2x=10

x= -5

Szczegółowe wyjaśnienie: